The Effects of Service Quality, Words of Mouth, and Satisfaction on Customer Loyalty at Ulfa Sukses Taylor - Laela Ulfa; Sri Rahayu; Dede Dede (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this study was to test and analyze service quality, word of mouth and satisfaction with consumer loyalty at Ulfa Sukses Taylor, East Lampung. This study uses a quantitative approach. The population and sample in this study are Ulfa Sukses Taylor customers. The sample is 50 people. The sampling technique uses the Non Probability Sampling technique, namely Purposive Sampling. To obtain primary data, questionnaires were distributed and the data obtained was analyzed using the SPSS statistical program. The test results and analysis show that service quality and WOM positive but not significant effect on consumer loyalty. On the other hand, consumer satisfaction has a positive and significant effect on brand loyalty. Simultaneous test results obtained service quality, WOM, and satisfaction have a positive and significant effect on consumer loyalty. This study has limitations on the number of respondents, although the number of 50 people is sufficient to be analyzed, the more the number of respondents, the better the results of the analysis. Therefore this research can be tested again for future research by increasing the number of respondents. The influence between variables that is not yet significant can be retested in different types of businesses such as motorcycle and car repair service businesses, salons and spas, bridal make-up, and other service businesses. The results of this research are of practical or managerial use, especially for Ulfa Sukses Taylor's business in Braja Luhur Village , East Lampung and other types of businesses. In this case the owner and manager of Ulfa Sukses Taylor needs to pay attention to the quality of service quality , word of mouth to increase consumer loyalty. Keywords: Comsumer loyalty, Consumer satisfaction, WOM, Service quality, Marketing Management